Profil Pakan Dari Limbah Sagu Tersubtitusi Limbah Tahu (Pakan Satu) dan Implikasinya Terhadap Pertumbuhan Ayam Pedaging - Abdollah, Azwar; Sohilauw, Indrayani Sima Sima; Warang, Azril Fajar; Wahyudi, Agus (Biosel Biology Science and Education, 2023)
One of the concepts of saving the environment is using waste as a basic material for making a product. An example of waste that can be used as raw material is tofu dregs which have chemical properties that are dominated by protein so that they can be processed into products that function as a source of protein. Another example is bran and sago dregs which still contain macro nutrients that are useful as nutritional intake for livestock. The nutritional content contained in tofu dregs, sago and bran has the potential to be developed as animal feed, especially poultry feed. The results of the research conducted revealed that fermented sago waste can be used as feed for poultry. stated that there was an increase in body weight of broiler chickens that were fed fermented tofu dregs with probiotic inoculum in the ration. The research results show that the nutritional content of tofu dregs is: 8.66% protein; fat 3.79%; 51.63% water and 1.21% ash so it has great potential to be processed into animal feed. The method used in this research is quantitative with an experimental approach which aims to determine the process of making animal feed from organic waste, analyze the quality of the feed, and analyze the effect of feeding on the increase in body weight of broiler chickens. Research results: From the results of the research, there is a nutritional content, namely calcium 15.10%, carbohydrates 6.76% and protein 15.3%. The increase in body weight in boiler chickens is that from the first week the average weight is 21-29 grams after being fed for 8 weeks, there is an increase in weight. namely 1.87gr. Keywords: Sago Waste, Tofu Waste, Animal Feed.